Psychological and Pedagogical Aspects of the Development of Integrative Readiness of Future Specialists for Professional Activity - Шевчук, Кристина (My University, 2020)
Theneedtodevelopanintegrativereadinessoffuturespecialistsisarelevantscientificproblem.Thereasonsforthiscouldbebasedonthefactthatthatthespecialists-to-bewereexpectedtobeinvolvedinthefiercecompetitionforvacanciesandareasofactivity,havemoderninformationandcommunicationtools,i.e.haveanintegrativereadinessforprofessionalactivity.Institutionsdonot,however,haveasingleintegration(interdisciplinary)frameworkfortraining,donotprovideacomprehensiveeducationalinformation,technicaltools,strategiesandtechnologiesofeducation,reasonedpsychologicalandpedagogicalconditions.Accordingtotheauthor,theintegrativereadinessoffuturespecialistsforprofessionalactivityisasystem-personalityformationthatreflectstheunityoftheoreticalandmanagerialtrainingandpracticalabilityofstudentstocomprehensivelyapplyregulatory,socio-economic,psychologicalandpedagogicalmethodsandtechnologiesforsolvingdifferentproblems.Thisreadinessreflectstheunityofthemotivationalinclinationoffuturespecialiststoprofessionalactivityandknowledgeofpracticaltechnologiesforsolvingawiderangeofprofessionalproblemsinpersonalandbusinessinteractions.Theresearchmethodologyisbasedontheconceptofkeycompetence,whichprovidessystematization,classificationofsignificantproblems,developmentofamatrixofsignificantproblems,anddeterminationofoverallstrategy,managementtechnologyofprofessionaltrainingdevelopmentprocess.Studentsandteacherscanuseresearchmaterialscanbeusedbyineducationalandpracticalactivities;developersofcontent,organizationalformsandmethodsofprofessionaltrainingtoimprovethepracticalcomponentofcurriculaandstandardsoftheirdevelopment
Keywords: Integrativereadiness,Futurespecialists,Psychological,Pedagogicalaspects,system-personalityformation,conceptofkeycompetence,Interdisciplinarybasisofprofessionaltraining